Shaykh Nawawi Al-Bantani’s Contribution to Grounding Shafi’i Islamic Law in the Indonesian Archipelago during the 19th Century - Imawan; Faiz; Herman; Masruri (Al'Adalah, 2024)
Shaykh Nawawi al-Bantani's contributions in the 19th century to grounding Islamic law in Nusantara mark a pivotal moment in Indonesian Islamic history. Despite previous research on his scholarly work and influence, studies have often focused on general education and tasawwuf, leaving a significant gap in analyzing his profound impact on Shafi'i jurisprudence and its integration into the Indonesian archipelago. This research addresses how al-Bantani facilitated the dissemination and popularization of Islamic law, mainly through his prolific writings and the network of students he mentored. By employing qualitative historical analysis, this study examines primary texts authored by al-Bantani, such as Nihayah al-Zain and Qut al-Habib, alongside secondary literature on his intellectual legacy. The analysis reveals al-Bantani's distinctive approach to bridging advanced Shafi'i jurisprudential concepts with practical applications, resonating with scholars and laypersons in the Indonesian archipelago. His works, widely adopted and taught by his students, stimulated a shift from a dominant tasawwuf-oriented framework to a jurisprudential focus in Islamic studies. This research underscores the necessity of revisiting the Indonesian archipelago's intellectual legacy to recognize its crucial role in modern Islamic discourse. Future studies should investigate al-Bantani's contributions comprehensively to other disciplines, such as hadith and theology, to illuminate his multifaceted legacy.